THE LEVEL OF KNOWLEDGE OF NURSERY OWNERS IN THE PRODUCTION AND MARKETING OF SAPLINGS - Kabir, Khondokar Humayun; Kashem, M. Abul.; M. Miah, M. Abdul. (European Scientific Journal, ESJ, 2013)
The purpose of this study is to determine the level of knowledge of nursery owners in the production and marketing of saplings. Ninety four nursery owners were selected randomly from a total of 157 nursery owners under four Upazila of Rangpur district. An interview scheduled was used for the collection of data in 2011; and the results shows that 63.8% of the nursery owners had medium level of knowledge, while 36.2% had high level of knowledge. Findings also shows that farm size, annual income ,innovativeness, communication exposure, training received, and involvement in nursery have positive significant relationships and constraints during production; and marketing has negative significant relationship with the level of knowledge of the nursery owners. However, the result of stepwise multiple regression indicates that 69.4% (Adjusted R2=69.4) of the variance in the level of knowledge of the nursery owners could be explained using the explanatory variables of the study. This indicates that there are other variables working behind the level of knowledge of the nursery owners during production and marketing.